2017
DOI: 10.4103/ija.ija_277_17
|View full text |Cite
|
Sign up to set email alerts
|

Adductor canal block for post-operative analgesia after simultaneous bilateral total knee replacement: A randomised controlled trial to study the effect of addition of dexmedetomidine to ropivacaine

Abstract: Background and Aims:Knee replacement surgery causes tremendous post-operative pain and adductor canal block (ACB) is used for post-operative analgesia. This is a randomised, controlled, three-arm parallel group study using different doses of dexmedetomidine added to ropiavcaine for ACB.Methods:A total of 150 patients aged 18–75 years, scheduled for simultaneous bilateral total knee replacement, received ultrasound-guided ACB. They were randomised into three groups -Group A received ACB with plain ropivacaine; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 23 publications
1
27
2
Order By: Relevance
“…The initial literature search identi ed 143 articles, of which 135 were excluded because they failed to meet the eligibility criteria. A total of 7 RCTs involving 546 participants were ultimately included in this meta-analysis (8)(9)(10)(11)(12)(13)(14). The PRISMA ow diagram is presented in Fig.…”
Section: Search Results and Risk Assessmentmentioning
confidence: 99%
“…The initial literature search identi ed 143 articles, of which 135 were excluded because they failed to meet the eligibility criteria. A total of 7 RCTs involving 546 participants were ultimately included in this meta-analysis (8)(9)(10)(11)(12)(13)(14). The PRISMA ow diagram is presented in Fig.…”
Section: Search Results and Risk Assessmentmentioning
confidence: 99%
“…The initial literature search identi ed 143 articles, of which 135 were excluded because they failed to meet the eligibility criteria or were duplicates. A total of 7 RCTs involving 546 participants were nally included in this meta-analysis (8)(9)(10)(11)(12)(13)(14). The PRISMA ow diagram is presented in Fig 1. The evidence quality and risk assessment were evaluated according to the Cochrane Collaboration's tool for assessing risk of bias.…”
Section: Search Results and Risk Assessmentmentioning
confidence: 99%
“…Total opioids consumption was recorded in 4 studies (8,9,11,12) containing patients. Pooled data indicated that there were signi cant differences between these two groups (SMD = -0.63[-0.86 to -0.40], P<0.01, I 2 = 0%, Fig 5).…”
Section: Total Opioids Consumption In 24 Hours Postoperativelymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 5 ] Second, it would be important to present the post-operative opioid consumption by study groups, as this can significantly alter the primary outcome. [ 6 ] Finally, the authors excluded patients who were at high risk for post-operative nausea and vomiting; and therefore, it is likely that their findings are not generalisable to other patients beyond the patients included in this study.…”
mentioning
confidence: 99%